Conrad and language - Baxter, Katherine Isobel, 1976-; Hampson, Robert (Edinburgh : Edinburgh University Press, 2016)
Opens up the rich topic of Joseph Conrad's complex relationship with language. Joseph Conrad was, famously, trilingual in Polish, French and English, and was also familiar with German, Russian, Dutch and Malay. He was also a consummate stylist, using words with the precision of a poet in his fiction. The essays in this collection examine his engagement with specific lexical sets and terminology - maritime language, the language of terror, and abstract language; issues of linguistic communication - speech, hearing, and writing; and his relationship to specific languages - his deployment of foreign languages, his decision to write in English, and his reception through translation. The collection closes with an Afterword by renowned Conrad scholar, Laurence Davies. Key Features. The first academic and critical study wholly devoted to the topic of Conrad and language, and the first to address that topic from a diversity of critical approaches Speaks to a range of current trends in literary criticism including transnationalism, lateness, translation studies, terrorism and disabilities studies Comprises newly commissioned essays by leading and emerging Conrad scholars from around the world, employing a variety of approaches including philosophy, psychoanalytical theory, biographical theory, as well as textually driven readings
A Note on Texts; Conrad and Language: Introduction, Katherine Isobel Baxter and Robert Hampson; Conrad and Maritime Language: Flying Moors and Crimson Barometers, Robert Hampson; 'I have something in hand that shall strike terror into the heart of these gorged brutes': The Many Meanings of Terror in Conrad's Fiction, Andrew Glazzard; Conrad, George Moore and the Critique of Abstract Language, John Attridge; Conrad´s Language of Passivity: Unmoving towards Late Modernism, Yael Levin; The Powers of Speech in Conrad's Fiction, Josiane Paccaud-Huguet; 'Soundless as Shadows': Language and Disability in the Political Novels, Katherine Isobel Baxter; Joseph Conrad and Romanized Print Form: from Tuan Almayer to Prince Roman, Chris GoGwilt; Languages in Conrad's Malay Fiction, Andrew Francis; Gallicisms: The Secret Agent in Conrad's Prose, Claude Masionnat; 'The speech of my secret choice': Conrad and English, Andrew Purssell; Recent Russian Translations of Under Western Eyes and The Secret Agent, Ludmilla Voitkovska; Afterword, Laurence Davies.
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Conrad, Joseph, -- 1857-1924 -- Language; Conrad, Joseph, -- 1857-1924; Conrad, Joseph -- 1857-1924; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh; Language and languages